MANAJEMEN PENINGKATAN MUTU KOMPETENSI LULUSAN BIDANG KEWIRAUSAHAAN DALAM MEMENUHI STANDAR NASIONAL PENDIDIKAN DI SMK ANNUQOYYAH GULUK-GULUK SUMENEP JAWA TIMUR - Maryatul Wakiah; Jamiludin Usman (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
Three problems become the main topic in this research, that is the description of management implementation, supporting factors, and inhibiting factors that are all related to improving the competency quality of graduates in entrepreneurship in meeting the national standards of vocational education An-Nuqoyyah Sumenep Guluk-Guluk East Java. This research method uses a qualitative approach with a phenomenological descriptive type. Sources of data obtained through interviews, observation, and documentation. The results showed that in implementing a program to improve the quality of graduates in the field of entrepreneurship at the Annuqoyyah Vocational School used four stages, that is (1). Planning by making school programs, organizing the division of tasks related to the field of entrepreneurship by using price labeling in the Marketing Laboratory. (2). The implementation consists of the preparation, follow-up, and evaluation stages of the entire program which is carried out mid and end of the semester. Supporting factors are (1). Openness and involvement of all teaching staff in building schools are even better; (2). There is support from Annuqoyyah boarding school caretakers. Furthermore, the inhibiting factors are inadequate infrastructure so that it can hinder students' learning and teaching processes; (2). Institutions that are not independent because there are still dependencies with pesantren foundations; (3). low student motivation and interest in learning results in neglect in the learning process; (4). The recruitment of less professional teachers makes some teaching staff do not match their expertise.